Sistem Informasi Pendataan Barang Server Berbasis Web Dengan Metode Extreme Programming Pada PT. Domestik Bentang Awan Teknologi - Sultan Marino; Jaka Sutrisna (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Current technological developments are very rapid in line with human needs for information that is used to support and solve problems in companies and society. PT. Domestik Bentang Awan Teknologi, which is one of the Information Technology and Cloud Computing based companies in Indonesia, already has inventory to store server goods. Data collection on server goods is still not optimal because it still uses conventional methods where there are errors or damage in data collection so that it is not effective and efficient in carrying out data collection on server goods. The process of collecting data on incoming and outgoing goods is quite long so that the data collection report process is hampered because it has to be input into Microsoft Excel. then you can make a report. Therefore, with the existence of problems, the creation of a Goods Data Collection Information System with computerized data processing is expected to provide information that is fast, precise, clear and directed. The system development method used is extreme programming and tested using black box testing and white box testing methods.